Solution of radiative transfer problems with finite elements - Kanschat, Guido (Numerical methods in multidimensional radiative transfer, 2009)
Mathematical modeling for monochromous radiative transfer problems is reviewed. Suitable boundary conditions for well-posed problems are introduced. Finite element discretizations for the integral operator in the angular variable and the transport operator in space are discussed. Adaptive algorithms and error estimates are explained. The structure of the resulting discrete linear system is analyzed and solution methods are suggested.
Gesehen am 26.06.2018